Causal associations between gut microbiome and cardiovascular disease: A Mendelian randomization study - Zhang, Yuxuan; Zhang, Xinyi; Chen, Delong; Lu, Jia; Gong, Qinyan; Fang, Jiacheng; Jiang, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Observational studies have suggested associations between gut microbiome and cardiovascular diseases (CVDs), but the roles of gut microbiome remain controversial, and these associations have not yet been ascertained causally. Methods: Two-sample Mendelian randomization (MR) was used to investigate whether gut microbiome causally affect the risk of CVDs. Two sets of MR analyses were conducted. A group of single nucleotide polymorphisms (SNPs) that less than the genome-wide statistical significance threshold (5 × 10-8) served as instrumental variables. To obtain a comprehensive conclusion, the other group where SNPs were smaller than the locus-wide significance level (1 × 10-5) were selected as instrumental variables. Summary-level statistics for CVDs, including coronary artery disease (CAD), myocardial infarction, atrial fibrillation, heart failure and stroke and its subtypes were collected. The inverse-variance weighted and Wald ratio methods were used for the MR estimates. The MR pleiotropy residual sum and outlier, weighted median, MR-Egger, leave-one-out analysis and MR Steiger were used in the sensitivity analysis. Results: Based on the locus-wide significance level, genetically predicted genus Oxalobacter was associated with an increased risk of CAD (odds ratio (OR) = 1.06, 95% confidence interval (CI), 1.03 – 1.10, P = 1.67× 10-4), family Clostridiaceae_1 was negatively correlated with stroke risk (OR = 0.83,95% CI, 0.75-0.93, P = 7.76× 10-4) and ischemic stroke risk (OR = 0.823,95% CI, 0.74-0.92, P = 4.15× 10-4). There was no causal association between other genetically predicted gut microbiome components and CVDs risk. Based on the genome-wide statistical significance threshold, the results indicated that there were no causal effects of gut microbiome on CVDs risk. Conclusions: Our findings reveal that there are beneficial or detrimental causal effects of gut microbiome components on CVDs risk and offer novel insights for exploring strategies to prevent and manage CVDs through the gut microbiome.